Evaluating different standard-setting methods in an ESL placement testing context. (July 2017) - Shin, Sun-Young; Lidster, Ryan
In language programs, it is crucial to place incoming students into appropriate levels to ensure that course curriculum and materials are well targeted to their learning needs. Deciding how and where to set cutscores on placement tests is thus of central importance to programs, but previous studies in educational measurement disagree as to which standard-setting method (or methods) should be employed in different contexts. Furthermore, the results of different standard-setting methods rarely converge on a single set of cutscores, and standard-setting procedures within language program placement testing contexts specifically have been relatively understudied. This study aims to compare and evaluate three different standard-setting procedures – the Bookmark method (a test-centered approach), the Borderline group method (an examinee-centered approach), and cluster analysis (a statistical approach) – and to discuss the ways in which they do and do not provide valid and reliable information regarding placement cut-offs for an intensive English program at a large Midwestern university in the USA. As predicted, the cutscores derived from the different methods did not converge on a single solution, necessitating a means of judging between divergent results. We discuss methods of evaluating cutscores, explicate the advantages and limitations associated with each standard-setting method, recommend against using statistical approaches for most English for academic purposes (EAP) placement contexts, and demonstrate how specific psychometric qualities of the exam can affect the results obtained using those methods. Recommendations for standard setting, exam development, and cutscore use are discussed.